2010
DOI: 10.1016/j.jvs.2009.10.116
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled study with intermittent mechanical compression of the calf in patients with claudication

Abstract: We concluded that the use of IMC of the calf for three months increased claudication distances and led to objective improvements in ABI-pe. Intermittent mechanical compression may be a useful approach to patients with continued claudication despite standard medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…In this animal model, a small blood pressure cuff (UPC3.3, 3.3 ϫ 12 cm; D. E. Hokanson, Bellevue, WA) is firmly wrapped around the left calf, and IPC is applied continuously for 150 min. This time duration is similar to that prescribed in the available clinical trials in stable claudicants (5,9,17). In healthy animals, this approach was reported to evoke leg blood flow responses analogous to that seen in humans under the same conditions (28).…”
Section: Animalssupporting
confidence: 68%
See 2 more Smart Citations
“…In this animal model, a small blood pressure cuff (UPC3.3, 3.3 ϫ 12 cm; D. E. Hokanson, Bellevue, WA) is firmly wrapped around the left calf, and IPC is applied continuously for 150 min. This time duration is similar to that prescribed in the available clinical trials in stable claudicants (5,9,17). In healthy animals, this approach was reported to evoke leg blood flow responses analogous to that seen in humans under the same conditions (28).…”
Section: Animalssupporting
confidence: 68%
“…Because IPC is homebased, this treatment strategy overcomes the major limitations associated with the surgical and noninvasive therapeutic options available for these patients, including low accessibility and unsatisfactory cost-effectiveness (6,17). Clinical trials in stable claudicants indicate that 3 mo of daily IPC application can increase maximal walking distance by ϳ110% (5,9,27), an improvement that is comparable to that obtained by supervised exercise training (17,32). Despite the growing clinical acceptance, the fundamental mechanisms by which IPC therapy promotes clinical benefits remain unclear.…”
Section: Application Of Intermittent Pneumatic Leg Compressions (Ipc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, here, we aimed to give fi rst evidence for long-term ISRT, and, indeed, we showed that walking distance improved with a more than two-fold increase in ICD and ACD in all of the tested PAD patients. Recent studies investigated the effect of diff erent compression devices on PAD patient outcome by focusing on peripheral perfusion and claudication pain [13,14]. Intermittent pneumatic calf and foot compression revealed a signifi cant improvement of the ICD and ACD after a daily treatment of 2 hours for 4 -6 months in a cohort of 30 patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Изначально метод наружной пнев-мокомпрессии использовался для улучшения веноз-ного кровообращения в конечностях пациентов, стра-дающих отеком нижних конечностей и/или имеющих риск развития тромбоза глубоких вен. Затем появи-лись работы, указывающие на новые возможности лечения для пациентов с ХОЗАНК [13][14][15].…”
Section: Discussionunclassified